Historia y literatura: maravillas, magia y milagros en el Occidente medieval, eds. Israel Álvarez Moctezuma, Daniel Gutiérrez Trápaga, México, UNAM, 2015, 267 pp. - Carla Calero Martínez; Andrea Martínez Latorre (Tirant)
-